2017
DOI: 10.1038/mi.2016.83
|View full text |Cite
|
Sign up to set email alerts
|

Age-related spontaneous lacrimal keratoconjunctivitis is accompanied by dysfunctional T regulatory cells

Abstract: In both humans and animal models the development of Sjögren syndrome (SS) and non-SS keratoconjunctivitis sicca (KCS) increases with age. Here, we investigated the ocular surface and lacrimal gland phenotype of NOD.B10.H2b mice at 7–14, 45–50, and 96–100 weeks. Aged mice develop increased corneal permeability, CD4+ T cell infiltration and conjunctival goblet cell loss. Aged mice have lacrimal gland (LG) atrophy with increased lymphocyte infiltration and inflammatory cytokine levels. An increase in the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 69 publications
(85 reference statements)
1
60
0
1
Order By: Relevance
“…161 Infiltration with autoreactive T cells and oxidative stress have also been observed in the aged lacrimal gland, indicating that aging is associated with inflammation and is not simply a degenerative process. 98, 137, 162166 These studies suggest that similar to the ocular surface, a vicious cycle of inflammation and apoptosis involving infiltrating cells and glandular acinar cells perpetuates LG inflammation leading to glandular dysfunction in SS and age-related dry eye.…”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 98%
See 2 more Smart Citations
“…161 Infiltration with autoreactive T cells and oxidative stress have also been observed in the aged lacrimal gland, indicating that aging is associated with inflammation and is not simply a degenerative process. 98, 137, 162166 These studies suggest that similar to the ocular surface, a vicious cycle of inflammation and apoptosis involving infiltrating cells and glandular acinar cells perpetuates LG inflammation leading to glandular dysfunction in SS and age-related dry eye.…”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 98%
“…Indeed, dysfunctional Tregs that cannot suppress T effector activity, but produce IFN-γ and IL-17 have been observed in mouse models of dry eye induced by desiccating stress or associated with aging. 123, 137 Furthermore, adoptive transfer of either T effectors or Tregs from aged mice into naïve immunodeficient recipient mice caused goblet cell loss and lacrimal gland infiltration, while the adoptive transfer T effectors or Tregs from young mice did not, suggesting that age-related Treg dysfunction may contribute to induction of dry eye disease. 137 …”
Section: Dry Eye – a Multifactorial And Self-perpetuating Inflammatormentioning
confidence: 99%
See 1 more Smart Citation
“…This important finding implies that Tregs may demonstrate function-specific impairment with age – their ability to control immune activation against infection and tumors might be intact, yet they fail to suppress IL-17-driven autoimmunity [56]. Using NOD.B10.H2b mice, Coursey and colleagues showed that dacryoadenitis in aging is associated with a significant increase in Treg frequencies, despite worsened lacrimal gland pathology [57]. Furthermore, the investigators identified a population of Tregs that, despite continued expression of Foxp3, had impaired suppressive function and expressed the pro-inflammatory cytokines IL-17 and IFN-γ.…”
Section: Tregs In Autoimmunitymentioning
confidence: 99%
“…Furthermore, the investigators identified a population of Tregs that, despite continued expression of Foxp3, had impaired suppressive function and expressed the pro-inflammatory cytokines IL-17 and IFN-γ. The pathogenicity of these inflammatory cytokine-producing Tregs was confirmed in adoptive transfer experiments, in which recipients of either aged Tregs or aged effector T cells developed DED, whereas recipients of young Tregs or young effector T cells did not [57]. The plasticity of Tregs towards an effector cell phenotype may be an important factor contributing to the increased prevalence of DED with age.…”
Section: Tregs In Autoimmunitymentioning
confidence: 99%